KARAKTERISASI DAN PEMANFAATAN ASAP CAIR DARI TEMPURUNG BUAH BINTARO ( Carbera manghas Linn.) SEBAGAI KOAGULAN GETAH KARET - Djeni Hendra; Totok K Waluyo; Arya Sokanandi (BRIN Publishing, 2014)
Smoke liquid is a condensation product of raw material combustion containing cellulose, hemicellulose and lignin. Itproduces many compounds that have antimicrobial, antibacterial, and antioxidant effect such as organic acids and itsderivatives. Bintaro fruit shell is a waste of oil processing bintaro that are not utilized. Generally, latex coagulation usesformic acid or acetic acid that it's expensive and less environmentally friendly. Bintaro shell pieces is unused material andcontaining cellulose, hemicellulose, and lignin made into smoke liquid that is acidic and could reduce pH so the latex willcoagulate faster. The purpose of this study was to use smoke liquid of shell bintaro fruit shell as an alternative coagulant forrubber latex material.Smoke liquid wasmade using a modified drum kiln with a temperature of 400 C for 7 hours. Smoke liquid is purifiedby distillation up to 200 C. Smoke liquid that has been purified, further analyzed of its physical properties such as watercontent, viscosity, specific gravity, pH, acidity and phenol. Application of smoke liquid as rubber coagulant where doneusing smoke liquid concentration of 5%, 10%, 15%, 20%, while smoke liquid from coconut shell was used as acomparison. The results showed that the best results for coagulating was obtained from bintaro shell concentration of 20%and the fastest time for coagulating obtained from coconut shell smoke liquid concentration of 5%. Bintaro shell smokeliquid can be used as a rubber coagulant but for coagulation time isnot as fast as coconut shell smoke liquid.